INKONSISTENSI PERATURAN PERUNDANG-UNDANGAN DALAM MEMANDANG KEABSAHAN PERKAWINAN BEDA AGAMA - Gina Hanifah; Flavia Faza Aulia; Denisa Juliani; Tiara Cahya Savitri (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Interfaith marriage is a phenomenon that often occurs in Indonesia. Legally, interfaith marriage is regulated in Article 2 paragraph (1) of the Marriage Law which states that marriage is legal, if it is carried out according to the laws of each religion and belief. This means that there is no marriage outside of religious law. But in reality, Law Number 23 of 2006 concerning Population Administration, which in one of its articles stipulates that interfaith marriages can be registered at the Civil Registry Office after obtaining a District Court decision. In this case there is an inconsistency in viewing the validity of the marriage. The purpose of this study is to examine the laws and regulations governing the validity of interfaith marriages so that it can be seen whether there are legal defects or legal weaknesses in these regulations. The research method that the author uses in this research is normative legal research (library), namely research that has an object of study on legal rules or regulations. Normative legal research examines the rule or rule of law as a system building related to a legal event.